The Antituberculosis Antibiotic Capreomycin Inhibits Protein Synthesis by Disrupting Interaction between Ribosomal Proteins L12 and L10 - Lin, Yuan (American Society for Microbiology, 2014)
Capreomycin is a second-line drug for multiple-drug-resistant tuberculosis (TB). However, with increased use in clinics, the therapeutic efficiency of capreomycin is decreasing. To better understand TB resistance to capreomycin, we have done research to identify the molecular target of capreomycin. Mycobacterium tuberculosis ribosomal proteins L12 and L10 interact with each other and constitute the stalk of the 50S ribosomal subunit, which recruits initiation and elongation factors during translation. Hence, the L12-L10 interaction is considered to be essential for ribosomal function and protein synthesis. Here we provide evidence showing that capreomycin inhibits the L12-L10 interaction by using an established L12-L10 interaction assay. Overexpression of L12 and/or L10 in M. smegmatis, a species close to M. tuberculosis, increases the MIC of capreomycin. Moreover, both elongation factor G-dependent GTPase activity and ribosome-mediated protein synthesis are inhibited by capreomycin. When protein synthesis was blocked with thiostrepton, however, the bactericidal activity of capreomycin was restrained. All of these results suggest that capreomycin seems to inhibit TB by interrupting the L12-L10 interaction. This finding might provide novel clues for anti-TB drug discovery.